2019
DOI: 10.1101/gr.241315.118
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between coding and exonic splicing regulatory sequences

Abstract: The inclusion of exons during the splicing process depends on the binding of splicing factors to short low-complexity regulatory sequences. The relationship between exonic splicing regulatory sequences and coding sequences is still poorly understood. We demonstrate that exons that are coregulated by any given splicing factor share a similar nucleotide composition bias and preferentially code for amino acids with similar physicochemical properties because of the nonrandomness of the genetic code. Indeed, amino … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…As exon recognition also depends on the binding to the pre-mRNAs of splicing factors that interact with compositionally biased sequences, one interesting possibility is that the nature of these splicing factors depends at least in part on the gene nucleotide composition bias. In this setting, we have recently reported that exons regulated by different splicing factors have different nucleotide composition bias [27].…”
Section: Introductionmentioning
confidence: 99%
“…As exon recognition also depends on the binding to the pre-mRNAs of splicing factors that interact with compositionally biased sequences, one interesting possibility is that the nature of these splicing factors depends at least in part on the gene nucleotide composition bias. In this setting, we have recently reported that exons regulated by different splicing factors have different nucleotide composition bias [27].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, coding exons can share the same nucleotide composition bias as their flanking introns and their hosting genes [79,255]. As a consequence, mRNAs produced from co-regulated genes share the same nucleotide composition bias and are likely regulated by the same set of RNAs binding proteins, that interact with nucleotide composition biased sequences, in agreement with the concept or RNA regulons [50,253,256,257]. Furthermore, since the genetic code is not random, coding sequences sharing the same nucleotide composition bias encode for proteins having the same amino acid composition bias or the same physicochemical properties (see main text).…”
Section: Appendix A1 Genome Physical Organization: From Gene Expresmentioning
confidence: 73%
“…Supporting the notion that constraints on the physicochemical properties of one kind of polymer affects composition biases of the cognate polymers are the following observations: (i) Nucleosome positioning leaves a footprint in protein sequences, (ii) splicing sites and splicing factor binding motifs constrain the amino acid composition of peptides encoded by splicing-regulated exons, and (iii) mRNA secondary structures depending on base complementarity have consequences on the secondary structures of the encoded protein [40,[49][50][51]. Conversely, protein secondary structures leave a footprint in the nucleotide composition bias of coding sequences, for example, amino acids that favor alpha-helices and beta-sheets correspond to codons ending with purines and pyrimidines, respectively [52].…”
Section: Interdependency Between the Physicochemical Properties Of Numentioning
confidence: 96%
“…F����������, � ������ ����� f���� ���� � ������������� f�����'� binding affinity in exons is weak, but improves in the noncoding sequences of DNA (22). It is quite possible that genetic variants may affect exonic splicing regulatory sequences and consequently disrupt pre-mRNA splicing and initiate genetic diseases (23,24).…”
Section: Discussionmentioning
confidence: 99%